Adam Mickiewicz’s Slavic theatre Concept (some reflections on a lecture given by the Polish Romanticist at the Collège de France in April 1843) - Hoffmann-Piotrowska, Ewa (ZFD 10: Zbornik radova s Međunarodnoga znanstvenog skupa Zadarski filološki dani 10 održanog u Zadru 10. studenoga 2023., 2026)
The article attempts to introduce the concept of Slavic drama and theatre, which is interesting in the context of Slavic studies, as presented during one of the lectures that the eminent Polish poet Adam Mickiewicz gave at the Collège de France. In his lecture delivered in April 1843, the poet initiated the great tradition of spiritual, metaphysical theatre, continued until the present day in Polish dramaturgy. Slavic drama is a small yet important element in the larger concept of Slavic culture, which were Mickiewicz’s lectures on Slavic literature from the years 1841–1844, in which he undertook the great effort to bring Slavic culture closer to the Western audience.